Hedges Function in Masculine and Feminine Feature’s Language: A Pragmatics Analysis - Azizah, Dinda Noor (Journal of Pragmatics Research, 2021)
The purpose of this study is to criticize the gender language features proposed by Coates (2013) proposed in Lakoff's theory (1975) by investigating speeches expressed by two different genders in interviews. The method used in this research is the descriptive qualitative method. Data were analyzed based on the theory of Coates (2013) to find language features based on gender and use the taxonomy of the hedging strategy proposed by Martin-Martin (2008). The results of the research show that male-female language features can be used by the opposite gender by looking at the perspective of the use of hedges and strategies in the concept of speech expressed by gender (male, female).Keywords: feature language; gender; hedges; hedging